Anatomy and histology of reproductive system of adult male mint leaf beetle Chrysolina herbacea (Duftschmid, 1825) (Coleoptera: Chrysomelidae). Issue 3 (25th September 2020) - Özyurt Koçakoğlu, Nurcan; Candan, Selami; Güllü, Mustafa
Abstract: In this study, anatomy and histology of the male reproductive system of Chrysolina herbacea (Duftschmid 1825) (Coleoptera: Chrysomelidae) are described and illustrated by using light and scanning electron microscopies. Data from the male gonad of this species provide more extended and precise knowledge regarding the histoanatomical structure of the reproductive system in Chrysomelidae. The male reproductive system in C. herbacea consists of paired bilobed testes, two paired vas efferentia, paired seminal vesicles, paired vas deferentia, paired tubular accessory glands, a ductus ejaculatorius, and an aedeagus. Each testis consists of 40 follicles enveloped in a yellow pigmented sheath. In the light and scanning electron microscope examinations of male reproductive system of C. herbacea, different spermatogenesis stages (spermatocytes, spermatids, and spermatozoa) are found. Each testes follicle joins with the vas efferens surrounded by monolayered cubic epithelium with oval nuclei. Epithelial cells are covered from the outside with a thin layer of muscle and sheath. Vas efferens connect to vas deferens that may have an enlarged and differentiated region = seminal vesicle. Mature spermatozoa are seen in the lumen of the vas efferens, seminal vesicle, and vas deferens. There is a pair of accessory glands with a convoluted appearance in the tubular structure around the vas deferens. The vas deferens is a straight tube which leads into the proximal end of the ductus ejaculatorius. Ductus ejaculatorius wall is surrounded by intima, monolayer epithelium, and a thick muscle layer with many nuclei. The distal section of the ductus ejaculatorius is housed within the aedeagus. Abstract : The different parts of male reproductive system in C. herbacea .